Irrigation Planning in the Era of Local Autonomy: An Analysis of Existing and Alternative Model* - SUGIYANTO, Eko; Djumadin, Zainul; DIGDOWISEISO, Kumba (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018, 2018)
The damage on irrigation networks has a massive impact on the decreasing quality of irrigation, which in turn has serious implications for the deceleration of farm productivity. One of the possible causes of such problem is related to the planning process in irrigation policy. This paper attempts to analyze existing model and provide the alternative model of irrigation planning in Indonesia through a qualitative approach in the area of West Java. In general, the existing model of irrigation planning is still territorial based on government affairs. For that, the alternative model should adopt a collaborative and spatial one.